Role of adjuvant therapy in resected stage IA subcentimeter (T1a/T1b) pancreatic cancer. Issue 1 (20th November 2018) - Shaib, Walid L.; Narayan, Amit Surya; Switchenko, Jeffrey M.; Kane, Sujata R.; Wu, Christina; Akce, Mehmet; Alese, Olatunji B.; Patel, Pretesh R.; Maithel, Shishir K.; Sarmiento, Juan M.; Kooby, David A.; El‐Rayes, Bassel F.
Abstract : Background: The standard of care for patients with resected stage I to stage III pancreatic ductal adenocarcinoma (PDAC) is adjuvant gemcitabine‐based chemotherapy. The role of adjuvant treatment in patients with subcentimeter, stage IA PDAC is unknown. The current study evaluated the effect of adjuvant treatment on survival outcomes among patients with American Joint Committee on Cancer/International Union Against Cancer stage IA (T1N0) resected PDAC using the National Cancer Data Base (NCDB). Methods: A retrospective review of the NCDB was conducted for patients diagnosed with T1 (tumor limited to the pancreas and measuring ≤2 cm in greatest dimension), lymph node–negative (N0), resected PDAC between 2004 and 2013. Patient demographics, histology, adjuvant treatment, and survival trends were examined. Kaplan‐Meier analysis and log‐rank tests were performed to determine the unadjusted association between overall survival (OS), tumor size, and treatment. Results: A total of 876 patients met the inclusion criteria. The patients had a mean age of 66.2 years (range, 32‐90 years); approximately 83.3% were white (730 patients) and 53.1% were female (465 patients). Approximately 45.9% of the patients had moderately differentiated tumor histology (402 patients); 70.0% (613 patients) had tumors measuring 1 to 2 cm (T1c) and 30.0% (263 patients) had tumors measuring <1 cm (T1a/T1b). Approximately 94.2% of patients had negative surgical margins (815 patients) and 46.9% (410 patients) received adjuvant therapy. The median OS was significantly different for patients who received adjuvant therapy compared with patients who did not (70.7 months vs 46.9 months; P = .0001). For patients with tumors measuring <1 cm, survival was not found to be significantly different between patients who received adjuvant treatment compared with those who did not (not reached vs 85.3 months; P = .54). In the multivariable analysis, none of the covariates (treatment group, Charlson‐Deyo Score, age, insurance, and facility status) demonstrated significant differences for patients with tumors measuring <1 cm. Conclusions: The current study is the first to demonstrate no survival benefit for adjuvant therapy in patients with resected subcentimeter PDAC. Abstract : The current original study is a treatment outcome analysis of the National Cancer Data Base of patients with resected, stage IA pancreatic ductal adenocarcinoma (PDAC). Although adjuvant treatment appears to demonstrate an overall survival benefit among patients with this stage of PDAC, when stratified by tumor size, patients with subcentimeter tumors (T1a/T1b) do not appear to benefit from adjuvant treatment. To the authors' knowledge, this is the first study to date to demonstrate no benefit for adjuvant treatment in patients with resected subcentimeter PDAC.